Computer-assisted total bilateral knee arthroplasty for a patient with severe hyperextension in residual poliomyelitis: a case report - Valery Y. Murylev; Semen S. Alekseev; Grigory A. Kukovenko; Pavel M. Elizarov; Dmitriy O. Golubkin; Aleksey V. Muzychenkov (Travmatologiâ i Ortopediâ Rossii)
Background. Total knee arthroplasty in patients in the residual stage of poliomyelitis is a technically difficult job. The reasons for this are anatomical features and therefore difficulties in an implant choice and conflicting results. In the present case report, we describe a unique method of a computer-navigated installation of a rotating-hinge implant in a non-standard position for a patient with residual poliomyelitis.